Making climate change policy work at the local level: Capacity-building for decentralized policymaking in Japan - Takao, Yasuo (The University of British Columbia, 2012)
This study will examine the state of local capacity building for local climate adaptation in Japan. Climate mitigation needs to be led by both global strategies and national mandates in an integrated way, but climate change impacts are manifested locally and adaptive capacity is determined by local conditions. The article first lays out the basic components of local capacity for decentralized policy making and assesses the current local capacity in view of Japan's climate policy. The bulk of data employed in the study is derived from existing up-to-date government databases. It found that only the largest municipalities as well as prefectures have governing capacities to develop a comprehensive approach to climate adaptation, while medium-sized municipalities have a potential to take a participatory approach to climate policy. It argues that some pioneering localities realize their potentials to take initiatives under political leadership but most localities act in a piecemeal fashion according to clear national-level guidance on climate change.